언어 네트워크 분석(Semantic Network Analysis)을 활용한 민간경비 분야의 연구 경향 - 양승돈(Seung-Don Yang) (한국콘텐츠학회 논문지, 13(11), 2013)
This study is aim to research trend of private security and to suggest direction of improvement to sector of private security. This study has been to analyzed to be useful social network analysis(particularly Degree Centrality and Clossness Centrality) for using typical research method about trend of academic subject. As a result of Degree Centrality and Clossness Centrality, Individual factors such as Job Stress and Job satisfaction of private security are more keyword than institutional factors and policy factors such as Security Services Industry Act and training for Private Security guards. It means that research trend of private security are to study Individual factors rather than institutional factors and policy factors. But, this study is a limit as follows; First, An object of study is only to searching article in National Assembly Liberary. A follow-up studies are need to expand the range of an object of study for private security. 이 연구는 민간경비 분야에 대한 연구 경향을 살펴봄으로써 민간경비 분야의 발전 방향을 제시하고자 하는 데 목적을 두고 있다. 연구 경향을 살펴보는데 있어 특정 학문이나 대상의 경향을 분석하는 대표적인 연구방법인 언어 네트워크 분석 방법 중 연결중앙성과 인접중앙성을 활용하여 분석하였다. 그 결과, 연결중앙성과 인접중앙성의 경우에서 직무스트레스, 직무만족와 같은 개인적인 요소들이 경비업법이나 경비원의 교육훈련과 같은 민간경비의 제도적 정책적 문제보다 더 많이 키워드로 나타났다. 이러한 결과들로 볼 때, 민간경비 분야 연구 경향에 있어 제도적 정책적 연구보다는 민간경비원의 개인적 요소에 관한 연구들이 많이 진행되고 있다는 것을 알 수 있다. 이 연구에서의 연구 대상이 국회도서관 내 검색된 연구결과물들만을 대상으로 했다는 점에서 일반화하기엔 한계가 있으며, 추후 그 연구 대상을 확대하여 좀 더 보완 확대할 필요할 것으로 보인다.